Quality of life patients after surgical treatment of laryngeal cancer (Journal of Medical Science, 2017)
Introduction. The assessment of the quality of life in cancer patients requires a multidisciplinary approach and an evaluation of emotional, social and physical conditions. Objectives. The aim of the study was to analyze the quality of life patients after surgical treatment of laryngeal cancer but before the next stage of therapy, i.e. radiotherapy. Material and Methods. The study group comprised 60 patients aged 44–82 years, with laryngeal cancer treated at the Radiotherapy Wards of Wielkopolskie Centrum Onkologii, Poznań, Poland. The Polish versions of the QLQ C-30 and the cancer-specific EORTC QLQ H&N35 questionnaires were used. Results. Mean score for the general health status (QLQ C-30) was 56.81. Mean values for the physical, role, cognitive, social and emotional functioning were 81.11, 80.83, 75.28, 70.00 and 54.72, respectively. The following constituted the main problems for laryngectomees: difficulty gaining weight (75.00), necessity to take nutritional supplements (58.33), sense of smell and taste problems (57.78), weight loss (56.67), articulation problems (56.67). A statistically significant difference (p = 0.002) was observed with regard to emotional functioning, with mean values of 28.83 and 60.51 for women and men, respectively. Also, a statistically significant difference (p = 0.01) was observed with regard to social functioning, with mean values of 45.53 and 75.51 for women and men, respectively. Conclusions. There exists a definite need to investigate the quality of life by means of patient self-evaluation of the symptoms in order to monitor patient status and establish an individual therapeutic, care and psychological approach.